1993
DOI: 10.1123/pes.5.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Parental Influence on Children’s Moderate to Vigorous Physical Activity Participation: An Expectancy-Value Approach

Abstract: This investigation examined parental influence on children’s moderate to vigorous physical activity (MVPA) participation via an expectancy-value model that included parents’ behavior, parents’ beliefs about their children’s MVPA, and children’s beliefs about their MVPA. The influence of parents on their children’s MVPA was investigated via questionnaires tapping the belief systems of fourth- and fifth-grade children (n=71) and their parents (n=69). Self-reported MVPA was assessed for parents and children. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1
12

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 19 publications
7
91
1
12
Order By: Relevance
“…Gustafson and Rhodes (2006), in their review of parental correlates in children's physical activity, found role modeling to be a potential mechanism to influence children's engagement in physical activity. Others have found there is inconclusive evidence to support a positive association between parental role modelling and children's activity levels (Biddle & Goudas, 1996;Dempsey, Kimiecik, & Horn, 1993;Garcia, Broda, Frenn, Coviak, Pender, & Ronis, 1995 A limitation of Warren's (2007) study was the difficulty in recruiting young caregivers to participate because, as previously mentioned, they are currently unidentified in society, but also because some participants reported they feared intervention would lead to family separation. As well, her interviews with the participants only lasted six minutes, which may not be enough time to gather the required information about caregiving tasks to make the conclusions she did.…”
Section: Importance Of Playmentioning
confidence: 98%
“…Gustafson and Rhodes (2006), in their review of parental correlates in children's physical activity, found role modeling to be a potential mechanism to influence children's engagement in physical activity. Others have found there is inconclusive evidence to support a positive association between parental role modelling and children's activity levels (Biddle & Goudas, 1996;Dempsey, Kimiecik, & Horn, 1993;Garcia, Broda, Frenn, Coviak, Pender, & Ronis, 1995 A limitation of Warren's (2007) study was the difficulty in recruiting young caregivers to participate because, as previously mentioned, they are currently unidentified in society, but also because some participants reported they feared intervention would lead to family separation. As well, her interviews with the participants only lasted six minutes, which may not be enough time to gather the required information about caregiving tasks to make the conclusions she did.…”
Section: Importance Of Playmentioning
confidence: 98%
“…Parent support may come in the form of positive role models, transportation, payment of fees, providing encouragement or motivation [27] . The physical activity levels of children's parents and siblings have a positive influence on their own participation in physical activity, just as the modelling of sedentary behaviours by parents and siblings influences a development of a sedentary lifestyle in children [28][29][30] . When children learn an appreciation for physical activity and when they learn how to participate in physical activities, they tend to be more physically active than their peers who are simply exposed to physical activity [31] .…”
Section: Parental Support Of Physical Activitymentioning
confidence: 99%
“…Gender differences in parental socialization influence have been reported in both academic (Eccles et al, 1984) and sport domains (Eccles and Harold, 1991). The model has also been successfully applied to studies of children's physical activity (Brustad, 1993(Brustad, , 1996Dempsey et al, 1993;Kimiecik et al, 1996;Kimiecik and Horn, 1998).…”
Section: Expectancy-value Theo Rymentioning
confidence: 89%